Economic Crisis Impact and Sustainable Development of Bulgarian Transport Sector: Current State and Development Trends - Nikolova, Hristina (Research Papers, 2014)
The paper explores the indicators and measures for economic sustainability of transport, with particular emphasis on the economic crisis impacts and opportunities for achieving economic sustainability. Several arguments substantiated by empirical evidence from Bulgarian transport sector development are put forward to demonstrate that current mega-trends in transport are at odds with a sustainable development and lead to high social costs. A variety of indices is discussed to improve the current threatening situation.The various paragraphs of this article concentrate on the real problems which performance of transport present to policy-makers and assess the contribution that the analysis can make to handling more effectively the transport system in Bulgaria.The aim of this article is to provide a general background against which the new research may be set. It does not aim either to be comprehensive in its treatment of sustainable development policy in transport or to provide answers of the questions that it or its paragraphs raise. It is hoped, however, that it may flag some of the key issues where uncertainty remains and where subsequent research could prove beneficial.